An investigation of the reading strategies used by ESL readers in comprehending a familiar and less familiar text - 357958 Zanariah Md. Saleh; Aston University (United Kingdom : Aston University, 1993)
This study was an investigation of the reading strategies employed by ESLreaders when comprehending two types of texts; familiar and a less familiar text. In particular, the study was an attempt to find out if there was any difference in the strategies used by the reader when comprehending the two texts, the variable being the presence of prior knowledge of the texts, the variable being the presence or prior knowledge of tht text's content in the former and the lack of it in the latter. Four subjects from the Faculty of Management and Human Resources were selected to read the texts. The familiar was taken from the subjects' content domain while the less familiar text was taken from the Mechanical Engineering field. The subjects were asked to verbalise their thoughts using the thinking aloud technique in the attempt to investigate the possible difference in strategy use. Findings fron the two readings were then compared to find out the possible difference and also similarities. The results of the study indicated that background knowledge was a significant factor that affected the strategies used by the readers in comprehending both types of texts.